B03 Analysis of a Huntington's disease knock-in mouse model designed to prevent the generation of the exon 1 HTT protein. (12th September 2022) - Papadopulou, Aikaterini-Smaragdi; Landles, Christian; Smith, Edward; Bondulich, Marie; Iqbal, Arzo; Osborne, Georgina F; Howland, David; Neueder, Andreas; Bates, Gillian P
Abstract : Background: In the presence of an expanded CAG repeat, activation of cryptic polyA sites in intron 1 of the huntingtin mRNA (HTT) generates HTT1a, a small transcript that is translated to produce the aggregation-prone and highly pathogenic exon 1 HTT protein. Aim: Assess the importance of exon 1 HTT in the pathogenesis of the disease and the value of HTT1a as a therapeutic target. Methods: All cryptic polyA sites were removed from intron 1 of Htt in the HdhQ150 knock-in mouse model by deleting approximately 20 kb DNA. Htt transcripts were measured by qPCR and RNAseq. HTT proteins were analysed by HTRF, immunoprecipitation, western blot and immunohistochemistry. Results: The deletion had no effect on Htt expression in the brain and periphery of wildtype animals. RNA analysis of the mice with the deletion (HdhQ150ΔI) suggested that intron 1 sequences were still present, and that cryptic polyA sites in intron 2 had been activated. However, protein analysis showed that exon 1 HTT was dramatically depleted in HdhQ150ΔI brains as compared to HdhQ150, while the levels of full-length HTT were comparable. Immunohistochemistry showed that HTT aggregation in the HdhQ150ΔI brains was considerably delayed over a 17-month time frame. Conclusions: The near ablation of exon 1 HTT in the HdhQ150 mouse model of HD greatly delayed the appearance of aggregated HTT in mouse brain regions. This supports the hypothesis that mutant exon 1 HTT initiates the aggregation process. The HTT1a transcript should be considered as a therapeutic target. Funding: CHDI Foundation.